Analyzing the constructs of stakeholder engagement towards renewable energy projects success in Malaysia: a PLS approach - M., Waris; Zarith Sufia, Azlan; Puteri Fadzline, Muhamad Tamyez; Ullah, Mehfooz; Khan, Asadullah (KnE Social Sciences, 2019)
Stakeholder engagement is increasingly becoming a part of practice in delivering successful project outcomes. However, there is a limitation of studies on how the stakeholder engagement approaches are being implemented primarily towards mega-scale projects such as renewable energy projects. This paper intends to fill the gap by analyzing the relationship between ten identified constructs of stakeholder engagement and renewable energy project success. Data was collected through survey questionnaires applied to the Renewable Energy Power Providers (REPPs) in Malaysia, using stratified random sampling. SPSS ver.23 and SmartPLS 3.0 was applied to test measurement and structural models of this study. The findings revealed that effective communication, continuous consultation, understand intention and behavior, implement plans, build good relationships, analyze changes, risk mitigation, compromise conflicts, understand project success and good project governance were significant critical constructs of stakeholder engagement that were confirmed as drivers that influenced the renewable energy project successfully. It is apparent that this study allows the contribution to the body of knowledge of project management and offers some important insights into limited literature on stakeholder engagement. This study also shed light on the key stakeholders’ groups in developing successful renewable energy projects.